Description of a new species of Paraxenylla (Collembola, Hypogastruridae) from Brazil, with comments on the genus - Queiroz, Gabriel C.; Deharveng, Louis (Zootaxa, 2008)
The genus Paraxenylla Murphy, 1965 is redefined and compared to Xenylla Tullberg, 1869 and Thibaudylla Najt & Weiner, 1997, its closest relatives. It is characterized by the differentiation of four thickened S-chaetae on the fourth antennal segment, modified mouthparts, the absence of empodial appendage, the presence of 5+5 eyes, the absence of anal spines and the anus in terminal position. P. sooretamensis sp. nov. is described, characterized by a reduced labial chaetotaxy, modified mouthparts, 6 axial chaetae on Th II–III and Abd IV, 4+4 chaetae on ventral tube and several other morphological features. Its chaetotaxy is very different from that of other Paraxenylla except P. arenosa Uchida & Tamura, 1967, resembling that of Xenylla or Thibaudylla. The new species was collected in forest litter about 40 km inland from the coast line of Espírito Santo, Brazil, while all other species of the genus live in littoral habitats. The three species Xenylla longicauda Folsom, 1898, X. occidentalis Womersley, 1933 and X. littoralis Womersley, 1933, that Palacios and Janssens (2006) considered to probably belong to Paraxenylla, do not fit the current definition of this genus (anal spines are present), and are either Xenylla or Thibaudylla. A key and a table of the 9 species of Paraxenylla are given.